URGENSI KEBIJAKAN PIDANA DALAM PEMBERANTASAN KORUPSI DI INDONESIA - Ketut Maha Agung (Jurnal Magister Hukum Udayana (Udayana Master Law Journal), 2015)
Corruption in Indonesia has been so severed and widespread in the community and veryalarming, its development continues to increase from year to year, both in number of casesand the amount of state financial osses and in terms of qauality. These criminal of fencescommit more systematic and scope into all aspects of life. Starting from lower level of thedominant and state officials or law inforcer. The constraints in the implementation of thecourt decision related to the return of states losses is convicted assets and property that hasbeen transfered. It’s ower problem in the law enforcement of corruption.It’s to ned of step ciminal polity to fight againts corrupiton to use of method is a system andmust to do is integrated from law inforcer and public society.